Pengaruh Self Assessment System dan Kualitas Pelayanan Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi - Faizal, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
Taxes are mandatory contributions of every citizen who is able to fulfill their obligations to the state, based on tax laws in Indonesia, tax payments use a self-assessment system, namely calculating, paying, and reporting taxes themselves. The purpose of this study is to analyze the effect of the self-assessment system on the level of compliance of individual taxpayers; analyze the effect of the quality of tax services on the level of compliance of individual taxpayers; and analyze the effect of the self-assessment system and the quality of tax services on the level of compliance of individual taxpayers at the Jember Pratama Tax Service Office simultaneously. The research method used in this study is quantitative research. The sample taken was 92 employees. While the data analysis is in the form of inferential statistics with the help of the SPSS version 23 program. The results of the study indicate that the self-assessment system partially has a significant effect on the level of compliance of individual taxpayers with a significance value of 0.000. While the quality of tax services partially does not have a significant effect on the level of compliance of individual taxpayers. Based on the determination coefficient test, R2 was obtained as 0.840, which means that simultaneously the influence of the self-assessment system and the quality of tax services have an effect on the level of compliance of individual taxpayers at the Jember tax service office by 84% and the rest is influenced by other variables not discussed in this study.